Lanreotide Induces Cytokine Modulation in Intestinal Neuroendocrine Tumors and Overcomes Resistance to Everolimus - Sciammarella, Concetta; Luce, Amalia; Riccardi, Ferdinando; Mocerino, Carmela; Modica, Roberta; Berretta, Massimiliano; Misso, Gabriella; Cossu, Alessia Maria; Colao, Annamaria; Vitale, Giovanni; Necas, Alois; Fedacko, Jan; et al. (Frontiers in Oncology, 2020)
Somatostatin analogues mantain their major role in the treatment of patients with advanced neuroendocrine tumors (NETs) and have multiple modulatory effects on the immune system. Here, we evaluated the effects of lanreotide treatment on expression of Th1, Th2 cytokine patterns in serum of patients with NET and in bronchial and pancreatic NET cell lines. Our results showed that lanreotide treatment promoted a Th1 cytotoxic immune-phenotype in patients with NETs originated by intestinal sites. Similar results were obtained also in vitro where lanreotide induced expression of Th1 cytokines (IFN-γ and TNFα) only in pancreatic and not in bronchial-derived NET cell lines. It seems, therefore, that cytokinomics can represent a useful tool for the identification of tumor biomarkers for the early diagnosis and evaluation of the response to therapy in NET patients. To avoid the drug-resistance induced by everolimus (mTOR inhibitor), we made the pancreatic NET cell line resistant to this drug. After treatment with lanreotide we found that the drug reduced its viability compared to that of sensitive cells. These data may have direct implications in design of future translation combination trial on NET patients.